Evaluating Synergistic Nephroprotective Effect of Parsley Extract and Ramipril in a Rat Model of Gentamicin-Induced Nephrotoxicity - Eisha Akram, Sadia Lodhi, Ayesha Aftab, Abdul Azeem, Anum Usman, Ayesha Sarwar, Ahsanullah Mirbahar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The kidney has an essential function in maintaining homeostasis by carrying out functions such as blood filtration, hormone synthesis, and drugs metabolism. This study is done to examine the combined effects of ramipril and parsley Leaves water-soluble extract on nephrotoxicity induced by gentamicin. Methods: A case control study was carried out at the Pharmacology Department Islamic International Medical College in collaboration with NIH Islamabad, from September 2019 to August 2020. This study was conducted with a sample of 50 healthy male albino rats. After collecting baseline measurements of urea and creatinine randomly, rats were divided into two groups. Group 1 was designated as the control group and remaining four groups were experimental groups. On day 35, the results were analyzed using biochemical parameters and histopathological evaluations. The statistical analysis was conducted using SPSS version 22. The One-way ANOVA test was applied to ascertain any variations in mean values. The post hoc Tukey’s test has been used to perform several comparisons among the groups. A significance level was p<0.05. Results: The treatment group 5, which received both parsley and ramipril, exhibited a significant decrease in serum creatinine and urea levels in nephrotoxic rats, in comparison to group 3 (Group treated with parsley) and group 4 (Group treated with Ramipril). It also exhibited significant improvements in histological evaluation. The group reported reduced indications of renal injury, including minimal infiltration of inflammatory cells, minimal vacuolation and necrosis. Conclusion: The current investigation has determined that the aqueous extract of parsley leaves and the drug ramipril both independently improve the nephrotoxic effects caused by gentamicin. Keywords: Gentamicin, Nephrotoxicity, Ramipril, Parsley leaves extract, Serum Creatinine & Urea level.